1999
DOI: 10.1681/asn.v1091921
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Ethnic Distribution of the G Protein β3 Subunit 825T Allele and Its Association with Obesity in Caucasian, Chinese, and Black African Individuals

Abstract: Abstract. Recently, it was demonstrated that one allele (825T) of the gene encoding the G protein β3 subunit (GNB3) is associated with hypertension in Germans. This study investigates a possible association with obesity in young male Germans, Chinese, and black South Africans with low, intermediate, and high 825T allele frequencies, respectively. In each of these three distinct cohorts, the 825T allele frequency was increased significantly in overweight (body mass index [BMI] ≥25 kg/m2) and obese individuals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The maternally active GNB3 gene lowers children's birth weight (Hocher et al, 2000). The low-birth-weight-risk allele has a frequency of 80% in Africans as opposed to 30% in Caucasians (Siffert et al, 1999); hence, this gene can explain a part of the lower birth weight of Black babies.…”
Section: Interracial Children and The Genetic Hypothesismentioning
confidence: 99%
“…The maternally active GNB3 gene lowers children's birth weight (Hocher et al, 2000). The low-birth-weight-risk allele has a frequency of 80% in Africans as opposed to 30% in Caucasians (Siffert et al, 1999); hence, this gene can explain a part of the lower birth weight of Black babies.…”
Section: Interracial Children and The Genetic Hypothesismentioning
confidence: 99%
“…According to the literature 825T allele frequency varies strongly depending on ethnicity and race. Homozygous 825TT genotype was found more often in Africa, where mutant allele frequency varies from 74% to 91% [10]. In Asian populations allele frequency is 46% (42%-55%) on average, in European original population 33% (21%-38%).…”
Section: Resultsmentioning
confidence: 96%
“…This association was also found in most other studies. Siffert W. et al [10] showed that the odds ratio to identify overweight in TT genotype tivity) [16,17], and in some of them this effect was enhanced by adding sibutramine therapy [17,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 825C > T SNP in the gene of the G-protein β3 subunit ( GNB3 ) has been linked to metabolic features such as hypertension, atherosclerosis and immunological response. The T-allele has also been associated with obesity risk in German, Chinese and South African populations ( Siffert et al, 1999 ). In pregnant women, carriers of the risk allele have a higher weight gain during gestation ( Dishy et al, 2003 ).…”
Section: Genetic Factors Associated With Gestational Diabetes Mellitu...mentioning
confidence: 99%